Great Bear Lake and Great Slave Lake Surface Temperature Retrieved from MODIS Aqua Data ... - Kheyrollah Pour, Homa; Attiah, Gifty (Borealis, 2024)
The Great Bear Lake and Great Slave Lake Surface Temperature (GBL_GSL_LST) dataset highlights the spatial distribution of lake surface temperature retrieved from MODIS Aqua Data from 2003 to 2023 for the Great Bear and Great Slave Lake in the Northwest Territories, Canada. The data consists of daily individual tiff files for both lakes. The dataset provides insights into the spatial and temporal changing trends of temperature on large Northern lakes. ... : Python, 3.8.2 ...